Impact of Covid-19 on the physical activity and well-being of Hungarian athletes and sports professionals - Szabó, T.; Stocker, M.; Ács, P.; Morvay-Sey, K.; Pálvölgyi, A.; Laczkó, T. (Health Problems of Civilization, 2020)
Background The COVID-19 pandemic had a significant effect on regular activities and lifestyles in Hungary in the second quarter of 2020. In this study, we identify the physical activity and mental well-being changes in the Hungarian sport sector.